Setting Positive Decision Which Fictitious In Act Number 30 Of 2014 On The Administration Of Government And Its Legal Consequences As The Object Of Dispute State Administration - Risky Amalia; Rakhmat Bowo Suharto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
Positive fictional setting in Act Number 30 of 2014 due to a legal fiction that require administrative authority to respond or issue a decision / action brought before it within the time limit as prescribed and if these prerequisites are not met, the administrative authority to grant deemed issuance of the decision / action filed legal to him. Fictitious such aims to provide assurance of the juridical side linked with a possible remedy to the court by parties who feel aggrieved, so that the silence of the administration equated with a written decision (written decision) that contains the approval even though his form is not physically written (unwritten decision). In brief,The issues raised 1) Why in Act Number 30 of 2014 on government administration is set on the fictitious positive decision 2) What about the legal consequences of the decision as a positive fictitious object of dispute TUN 3) What problems arise from a fictitious setting positive and what policy solutions need to be taken to overcome these problems. Aim to determine, analyze and assess the background and reasons underlying positive fictional setting in Act Number 30 of 2014 on public administration and to determine the legal consequences of the decision as a positive fictitious object of dispute TUN, and knowing what the problems arising from the positive fictional setting. This thesis research method using normative juridical approach, normative legal research resources obtained from the library instead of the field, for the term that is known is the legal material. the normative legal research library materials is a basic material in the science research generally called secondary law. From the research results can be concluded that Fictitious setting positive consequences on the object of dispute in the State Administrative Court in the attitude of the state administration officials ignored requests citizens to a decision issued after the enactment of Act No. 30 of 2014 on Government Administration using test models in the form of an application to the State Administrative Court as provided for in Article 53 of Act Number 30 of 2014 are not formulated norms regarding procedural law petition fictitious positive this makes the Supreme Court Supreme Court Regulation Number 5 of 2015 as a guide for the State Administrative Court judge in resolving disputes positive fictitious petition the Court shall decide upon a maximum of 21 (twenty one) working days after the application is submitted and the decision is final and binding.Keywords: Setting Decision; Fictitious Positive; Object Dispute